LINGUOCULTURAL ANALYSIS OF PRAISING WORDS IN ENGLISH AND UZBEK LANGUAGES - Norkobilova Nigora Uralovna, (World Scientific Research Journal, 2025)
Annotation. This article investigates the linguocultural characteristics of praising words in English and Uzbek languages. It explores how praise functions as a linguistic and cultural phenomenon, reflecting the values, traditions, and social norms of both nations. Through a comparative analysis, the research identifies similarities and differences in the semantic structure, pragmatic use, and cultural symbolism of praising expressions. The findings demonstrate that praise is deeply rooted in national mentality, communication styles, and moral standards.